Viral persistence: immunologic and molecular-genetic aspects of pathogenesis - O. B. Zhukova; N. V. Ryazantseva; V. V. Novitsky (Бюллетень сибирской медицины)
In the article a view of investigators on the modern understanding of long-term viral persistence forming mechanisms on cellular and molecular levels has been presented. A question on the role of persistent virus in the induction of changes in cellular differentiation character, of chromosome apparatus and of apoptosis of peripheral blood lymphocytes has been discussed.